Secular Evolution of Galaxies 2013
DOI: 10.1017/cbo9781139547420.008
|View full text |Cite
|
Sign up to set email alerts
|

Star formation rate indicators

Abstract: If we are to develop a comprehensive and predictive theory of galaxy formation and evolution, it is essential that we obtain an accurate assessment of how and when galaxies assemble their stellar populations, and how this assembly varies with environment. There is strong observational support for the hierarchical assembly of galaxies, but by definition the dwarf galaxies we see today are not the same as the dwarf galaxies and proto-galaxies that were disrupted during the assembly. Our only insight into those d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
191
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(203 citation statements)
references
References 168 publications
(239 reference statements)
7
191
1
4
Order By: Relevance
“…Assuming a factor of 2.5 conversion from Helou et al (1988) to total infrared flux, and Kennicutt (1998b) conversion to SFR we obtain a SFR of 14 and 4 M yr −1 , for NGC 4676A and B respectively. Combining Hα luminosity with our own estimate of IRAS total infrared flux from template fitting between 8−1000 μm and the conversion given by Calzetti (2013) results in a lower total SFR for the two galaxies, but consistent within the scatter of the other measurements.…”
Section: Multiwavelength Analysis Of Total Star Formation Ratessupporting
confidence: 81%
“…Assuming a factor of 2.5 conversion from Helou et al (1988) to total infrared flux, and Kennicutt (1998b) conversion to SFR we obtain a SFR of 14 and 4 M yr −1 , for NGC 4676A and B respectively. Combining Hα luminosity with our own estimate of IRAS total infrared flux from template fitting between 8−1000 μm and the conversion given by Calzetti (2013) results in a lower total SFR for the two galaxies, but consistent within the scatter of the other measurements.…”
Section: Multiwavelength Analysis Of Total Star Formation Ratessupporting
confidence: 81%
“…Amblard et al 2010, Bourne et al 2012, Dariush et al 2011, Smith et al 2012). In addition, empirically constrained proxies for star formation rates based on a variety of observational tracers are in common use (see Buat et al 2010, Kennicutt & Evans 2012, Calzetti et al 2013. However, all these techniques are unable to consider 1) the effect of non local contributions to the scattered and dust reradiated starlight at specific positions within a galaxy, 2) the intrinsic geometry of stellar and dust distribution and 3) the differences in observed emission due to different galaxy inclinations.…”
Section: Introductionmentioning
confidence: 99%
“…The SEDs of the simulated galaxy have been used by several authors to elucidate the dependence of multiwavelength emission from galaxies on their intrinsic physical properties (e.g. Hayward et al 2012, 2013, Chakrabarti & Whitney 2009, Jonsson et al 2010, Domínguez-Tenreiro et al 2014. One advantage of performing radiative transfer calculations for numerically simulated galaxies, which has not been considered very much so far, is that one can also study the predicted observed properties of these galaxies on local scales.…”
Section: Introductionmentioning
confidence: 99%
“…The 8 µm mid-infrared emission is generally considered to trace the PAHs heated by UV photons (Leger & Puget 1984;Sellgren 1984). It is thought that 2/3 of the 8 µm emission from a galaxy originates from heating by stellar populations 100 Myr or younger (Calzetti et al 2005;Calzetti 2013), and that PAH emission is stronger for increasing metallicity and dust content of the interstellar medium (e.g., Engelbracht et al 2005;Marble et al 2010;Calzetti 2013). The 24 µm emission is generally produced by dust following absorption of UV photons emitted by young stars, and traces SF on a time scale of 10 Myr (Calzetti et al 2005;Leroy et al 2008).…”
Section: Ancillary Optical and Infrared Imagesmentioning
confidence: 99%